2023
DOI: 10.1021/acsami.3c00708
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Electrocatalytic Formic Acid Oxidation Activity via P-PdAuAg Quaternary Alloying

Abstract: Direct formic acid fuel cells (DFAFCs) are considered promising sustainable power sources due to their high energy density, nonflammability, and low fuel crossover. However, serious CO poisoning and activity attenuation of the anodic formic acid oxidation reaction (FAOR) greatly restrict the output and durability of DFAFCs. Inspired by the specific relationship between the composition, type, and property of alloys, in this work, we synthesize a series of hybrid substitutional/interstitial quaternary alloys P-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Pang et al developed the (Fe 0.14 Ni 0.47 Co 0.39 ) 2 P catalyst, which had high activity in electrocatalytic water splitting. Huang et al developed P-PdAuAg nanocomposites, which showed enhanced activity in formic acid oxidation reactions.…”
Section: Electronic Effects: Electron Withdrawingmentioning
confidence: 99%
“…Pang et al developed the (Fe 0.14 Ni 0.47 Co 0.39 ) 2 P catalyst, which had high activity in electrocatalytic water splitting. Huang et al developed P-PdAuAg nanocomposites, which showed enhanced activity in formic acid oxidation reactions.…”
Section: Electronic Effects: Electron Withdrawingmentioning
confidence: 99%
“…15 Zhao and coworkers prepared the P-PdAuAg quaternary alloy with a diameter of only 3 nm and abundant defects, demonstrating both activity and antipoisoning capabilities far exceeding those of currently reported formic acid oxidation catalysts. 16 Despite the successful demonstration of their superior electrocatalytic performance over monometallic counterparts, most products in these studies were small particles lacking well-defined morphology, which hindered systematic investigation into the relationship between structure (i.e., facets and/or porosity) and properties. Thus, there remains a need for an effective method to control the morphology of multimetallic nano-alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The former deliver high specificity, sensitivity, and wide response range. [ 7 ] However, due to the inherent instability of the enzyme molecule, they are sensitive to changes in environmental conditions (e.g., temperature, humidity, and pH). [ 8 ] In addition, enzymes also have the characteristics of high cost and difficult preservation, which limit the development of enzyme‐based electrochemical Glu sensors.…”
Section: Introductionmentioning
confidence: 99%